VII a. pirmosios pusės karys iš Lazdininkų (Kalnalaukio) - Bliujienė, Audronė; Butkus, Donatas (Archaeologia Lituana, 2002)
Rich warrior grave 73 was found in the south–eastern part of the cemetery within excavations of 2000 (KrM LS 2561/196–215). Diseased persons was buried in a grave pit which has measures of 275 x 54 cm and was deep of 86 cm. Diseased individual was put into the hollowed – out log coffin and buried at the beginning of the summer. About the time of bury possible to know from ripening of a maple seed (Acer platanoides). Maple seed was found between belt plates. Enough big parts of the hollowed – out log coffin was discovered in preparation of the grave 73 in the deep of 60–65 cm. From a skeleton of diseased person survived only upper part of death’s head, fragment of upper maxilla and two teeth. From the other parts of the skeleton was found fragments of femur skin – bone and bones of the left hand. The burial posture of the diseased person permit to maintain that head of individual was orientated to north–west (280°). Diseased individual was buried in extended position, right hand was put on the breast of the buried individual; left hand was extended (fig. 1). At Lazdininkai grave 73 was buried individual about 20–25 years old, according to the grave goods male. In was mentioned that it has been tried to disentomb the burial. Phenomenon of such disentombing is not clear enough. Traces of bronze drinking horn orifice binding and the remains of the clay pot miniature were found in the end of hollowed – out log coffin above the head of the buried individual, in the left side (fig. 1:1–2). Two spearheads there were discovered at the left side of the buried individual head on the coffin side (fig. 1:4–5; 2:1–2). One of the spearheads was 27,5 long with a pronounced mid rib. Another spearhead was 60,5 cm long, with very narrow upper part. This spearhead should be ascribed to the type I d, according to Lithuanian weapons typology. However, there are not so long spearheads found in Lithuania before. Iron-socketed axe, scythe, riding bit with a three-jointed mouthpiece and sandstone whetstone was put above the head diseased person (fig. 1:6–9; 2:3, 5–7). Small truncated biconical, lathed amber bead was found near the maxilla of buried individual (fig. 1:10; 8:3). Three fibulae have been fastening cloth of the buried individual on a breast (fig. 1:11–13; 6, 8). One of them crossbow zoomorphic brooch is 13 cm length; width of an axis is 13,6 cm (fig. 1:11; 6). The foot, bow, spiral and end knobs of axle are made from bronze; axis and pin are produced from iron. Two silver rings ending the fibula foot. Head of an animal with elongated eyes adorned fibula foot. Eyes of animal are made from blue glasses. Two different relief geometrical motifs decorated the bow and foot of the brooch. Metopine plate, covered by silver plate with blue glass adorned bow of crossbow zoomorphic fibula. The variety of metals and blue glasses of crossbow zoomorhpic fibula, gives possibility established stylistic links with hunic polichromic style of the fifth–sixth centuries and latest Germanic cloisonné style. The crossbow zoomorphic fibula is dated to the first half of the seventh century. Two others bronze crossbow fibulae with ladder fastened cloth of buried individual (fig. 1:12–13; 8:1–2). Both fibulae belong to the earliest type of such brooches and have been dated to the second half of the sixth century–seventh century. Two bronze spiral rings adorned the left hand of the buried individual (fig. 1:18–19; 8). One bronze spiral ring was on the right hand of the buried individual (fig. 1:18–19; 8:2). One-edged sword with splendid scabbard and strap-handle was put on the breast of buried individual (fig. 1:15, 3). The sword is 54,5 cm long; width of blade is 3,5 cm. One-edged sword blade long 44 cm. Sword does not has cross-guard. Such sword is dated to the fifth–eight centuries in Lithuania. Curonians started to use one-edged sword in the first half of the seventh century. One edged sword was put into a very richly adorned scabbard. Scabbard, perhaps were made from wood. Four zoomorphic pendants were hung to scabbard. Straphandle was fastened scabbard to the belt. Spacer rosettes, silver bindings, bronze rivets adorned strap-handle belts (fig. 3). There were found the details of the belt in the area of the waist and knees (fig. 1:17; 4). The belt has fifth bronze openwork belt plates and silver belt plates (fig. 4:3–5). Bronze openwork belt plates were found under silver ones. Belt has bronze covered by silver plate end of irregular shape (fig. 4:2). Four lancets shaped pendants were a part of the belt embellishment (fig. 4:6). The one-edged sword through the system of the small belts was hang up to the splendid belt. Smaller hafted knife was found beside the one-edged sword (fig. 1:16; 2:4). Chronology, social and ethnical dependence of the buried individual. Abundant, without analogues in Lithuania, grave goods show that at Lazdininkai grave 73 was buried noble warrior, horseman, who has connections with western Mazurian Lakeland, Sambian Peninsula and Gotland (fig. 1–9). One-edged swords are known from the sixth–eighth centuries in the territory of the Baltic tribes. The spearheads found in the grave are characteristic to the sixth–seventh centuries. The order of the putting of the additional grave goods (spear heads, socketed axe, scythe, riding bit, whetstone) – in the left side above the head of the buried individual – is characteristic to the cemeteries of the Lithuanian seaside not only in the Roman Iron Age and Migration Period, but also to the burials of Curonian warriors in the seventh–ninth centuries. Such funeral elements as position of the drinking horn above the head of the buried individual, belt place on the breast of the buried individual are common Curonian burials. The bronze openwork belt plates and lancet shaped pendants shows point close connections of buried individual to Mazurian Lakeland, Sambian Peninsula, and Scandinavia. Geometrical motifs of some details on scabbard and crossbow zoomorphical fibula (“the gees feet”; fig. 5) were known only from the archaeological material of the fifth–sixth century. Until now, V type plaited pattern was known only from the Southern Curonian burial sites of the eight–ninth centuries. Conclusions: Noble warrior was buried at Lazdininkai cemetery, grave 73, in the first half of the seventh century. Evidentially, young man from Lazdininkai grave 73 has been belonging to warrior elite of western Balts society. Such complex of grave goods is found for the first time in Lithuania. Archaeological material from Lazdininkai fills up the chronological gap between graves of sea coastal Lithuania cemeteries and Curonian burials. All grave goods found in the grave 73 show development of artefact types, forms and stylistic peculiarities and links with other regions in the end of the sixth–the first half of the seventh century. This fact also gives possibility to make conclusions about sources on which ethnical bases Curonian’s build their society.